ANALISA DISTRIBUSI AIR BAWAH TANAH DI KELURAHAN TANGKERANG LABUAI MENGGUNAKAN METODE COOPER-JACOBS DAN GEOLISTRIK KONFIGURASI SCHLUMBERGER - Suryadi Simbolon; Usman Malik (Universitas Riau, 2022)
Groundwater, one part of water resources is the most needed by humans for life. The availability of ground water and the increasing population growth in Tangkerang Labuai Village reguire the use of clean water. This study aims to determine the rock layers that makes up the soil and soil aquifers and the quality of groundwater. For the soil layer, it user the Schlumberger configuration geoelectric method,for the aquifer test, uses the Jacobs step drawdown method to determine the decrease of groundwater level is time. For air quality uses radians where the pH, TDS, turbidity values describe the resistivity value. The results of the research based on data processing on a 90 m long track,ground water is found at a depth of 7-10 m with a resistivity value of 114 m, which is categorized as granite, sand, gravel, alluvium constituent layers with a resistivity value of < 1000 m or the aquifer is partially connected due to the presence of a porous rock layerhaving small pores. To test the aquifer in the well based on the relatively small decrease in groundwater, namely 0.2 and 0.1 cm with a discharge of 0.43 liter/second with a transmissivity value of 971.901 m2/day, categorized as free or connected aquifer. Groundwater could not be consumed from the results as as stated to the regulation of the Minister of Health of the Republic of Indonesia number 492 of 2010, because the pH obtained was < 6.5 or acidic nature and categorized as partially connected aquifers because the more acid of water is formal, the higher the resistivity value is obtained.